Stunting in Eastern Indonesia: Determinants and Solution from Indonesian Family Life Survey - Mochamad Thoriq Akbar; Dharra Widdhyaningtyas Mahardhika; Estro Dariatno Sihaloho (Jurnal Cita Ekonomika, 2021)
Stunting is considered as detrimental and worrying health problems in many developing countries. WHO in 2018 reported that Indonesia ranks 3rd as country with highest stunting prevalence in Southeast Asia and it is dominated in eastern region of Indonesia with the highest prevalence rate in East Nusa Tenggara (40.3%) This study aims to find determinants and solutions related to stunting of children aged 0-59 months in eastern region of Indonesia. Using 1093 samples of children aged 0-59 months from Indonesian Family Life Survey (IFLS) East 2012, this paper used logistic regression to find relationship between socio-economic factors and household characteristics to stunting dummy variable. This paper found that paternal education, birth order, quality of sanitation, maternal Body Mass Index (BMI), and relative wealth using Principal Component Analysis (PCA) are significantly correlated with stunting.